2021
DOI: 10.1186/s13018-021-02380-y
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in pediatric hand fracture incidence in Malmö, Sweden, 1950–2016

Abstract: Background The hand is the second most fractured region in children. It is therefore important to update fracture epidemiology to be able to identify time trends for adequate health care planning. This study reports pediatric hand fracture incidence 2014–2016 and, using published data, also long-term time trends in 1950–2016. Patients and methods The Swedish city of Malmö, with 328,494 inhabitants in 2016, has only one hospital. We used the hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Overall, these studies found that males are more vulnerable than females, older children are more likely to be injured, and the fifth finger and proximal phalanx are more frequently involved, which is similar to our results. In addition, eight out of nine studies reported a higher incidence of sports-related injuries than our series [3–5,7,9,18–20]; and Mirdad [8] reported that crushing is the most common aetiology of PHF. Different fracture characteristics among the studies are likely to be influenced by the different ages and types of activities, including sports, of patients.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Overall, these studies found that males are more vulnerable than females, older children are more likely to be injured, and the fifth finger and proximal phalanx are more frequently involved, which is similar to our results. In addition, eight out of nine studies reported a higher incidence of sports-related injuries than our series [3–5,7,9,18–20]; and Mirdad [8] reported that crushing is the most common aetiology of PHF. Different fracture characteristics among the studies are likely to be influenced by the different ages and types of activities, including sports, of patients.…”
Section: Discussionmentioning
confidence: 46%
“…We compared nine published studies from other countries according to age, mechanism of injury and fracture pattern [3][4][5][7][8][9][18][19][20] (Table 3). Overall, these studies found that males are more vulnerable than females, older children are more likely to be injured, and the fifth finger and proximal phalanx are more frequently involved, which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Open traumatic injuries are usually associated with crush, clean cuts, and avulsion injuries. Generally, displaced bone fractures are managed by displacement reduction and bone fixation 1) while paying attention to the vascularization of the finger. Clinical findings, such as cyanosis or pallor, decreased capillary refill, and numbness, indicate a possible decrease in blood supply to the injured finger owing to disturbances in flow from both the radial and ulnar digital arteries.…”
Section: Introductionmentioning
confidence: 99%